(untitled) (Mongolian Journal of Geography and Geoecology, 2025)
The study could be a basis for designing and choosing appropriate economic valuation methods for ecosystem goods and services in Mongolia. Ecosystem economic valuation is an effective way to measure and understand the significance of the benefits people receive from ecosystems. Gross Ecosystem Product (GEP) is the monetary value of ecosystem services, making the findings comparable to GDP. The GEP concept seeks to employ specific indicators to quantify the economic value of all ecosystem products and services. GEP is the total value of final ecosystem goods and services supplied to human well-being in a region annually. We have developed the first GEP framework for Mongolia and conducted a case study using the market valuation method, shadow engineering method, replacement cost method, avoided cost method, conservation value method, and travel cost method. The GEP was calculated at the provincial level, and a framework was customized for the unique economic and ecological situations of Khovd Province. Our findings revealed that the total GEP in Khovd Province ranged from 110040.7 million dollars to 113650.2 million dollars in 2015 and 2020, respectively. The GEP to GDP ratio varied between 815 and 390 during this time. Among the different components of GEP, the value of ecosystem regulating services played a crucial role, accounting for 99.6% equally in both 2015 and 2020. The research results show that the distribution of GEP components in Khovd province is entirely distinct. The contribution of soil conservation services is the highest to the GEP of the selected case.